Les réseaux de neurones artificiels - Aurore Schmitt; Benoit Le Blanc; Marc-Michel Corsini; Caroline Lafond; Jaroslav Brůžek (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The use of artificial neural networks (ANN) has grown in the last few years in many fields of research, but not in biological anthropology. They are a relevant alternative to current statistics for data processing. This note provides a background for understanding the notion of ANN and describes also few applications close to biological anthropologal topics.